Enhancing Oral Communication in English as a Second Language (Journal of Tikapur Multiple Campus, 2025)
Oral communication is a cornerstone of English as a Second Language (ESL) education. It plays an important role in helping learners communicate effectively and adapt to real-life situations. This study explores innovative methods for teaching oral communication, such as task-based learning, role plays, use of technology, Audio-Lingual Method (ALM), and collaborative activities like presentation, group work, etc. in ESL classrooms. These methods aim to improve students' oral communication skills, fluency, confidence, and practical language use. Although the demand for English proficiency is growing in both academic and professional settings, several challenges affect the teaching of speaking skills. These challenges include large class sizes, lack of resources, limited teacher training, etc. The study highlights the importance of speaking skills in ESL education and shows how teaching methods can vary in different contexts. It addresses the lack of specific courses or prescribed materials for developing speaking skills, emphasizing the influential role of motivated teachers in engaging students and fostering basic to advanced language proficiency. The study further aims to identify essential strategies and skills for teachers in teaching oral communication in second-language classrooms. The findings may help guide recommendations for curriculum changes, teacher training programs, and improved access to teaching resources. By adopting interactive approaches, ESL education can better prepare learners to succeed in a globalized world.